Juxtaposing Medical Centers Using Different Questionnaires Through Score Predictors - Puga, Clara; Schleicher, Miro; Niemann, Uli; Unnikrishnan, Vishnu; Boecking, Benjamin; Brueggemann, Petra; Simoes, Jorge; Langguth, Berthold; Schlee, Winfried; Mazurek, Birgit; Spiliopoulou, Myra (Frontiers in Neuroscience, 2022)
Background Chronic tinnitus is a clinically multidimensional phenomenon that entails audiological, psychological and somatosensory components. Previous research has demonstrated age and female gender as potential risk factors, although studies to this regard are heterogeneous. Moreover, whilst recent research has begun to identify clinical “phenotypes,” little is known about differences in patient population profiles at geographically separated and specialized treatment centers. Identifying such differences might prevent potential biases in joint randomized controlled trials (RCTs) and allow for population-specific treatment adaptations. Method Two German tinnitus treatment centers were compared regarding pre-treatment data distributions of their patient population bases. To identify overlapping as well as center-specific factors, juxtaposition-, similarity-, and meta-data-based methods were applied. Results Between centers, significant differences emerged. One center demonstrated some predictive power of the patients of the other center with regard to questionnaire score after treatment, indicating similarities in treatment response across center populations. Furthermore, adherence to the completion of the questionnaires was found to be an important factor in predicting post-treatment data. Discussion Differential age and gender distributions per center should be considered as regards RCT design and individualized treatment planning.